Neurogenic bladder in an adolescent managed by vesicostomy - Nerli, R B; Deole, Sushant; Patel, Priyeshkumar; Ghagane, Shridhar C; Hiremath, Murigendra B; Dixit, Neeraj S (Indian Journal of Child Health, 2020)
The child with a neuropathic or neurogenic bladder requires dedicated care throughout his/her lifetime. Every patient presents with a unique physiology and each phase in their life brings along varying challenges. The primary concern is their renal health, but continence and independence also play significant roles. Although most patients can be managed conservatively, a number of surgical options are also available to manage incontinence. Appropriate pre-surgical planning is required to ensure that the best treatment may be provided. It is important to understand associated potential complications. Long-term follow-up and surveillance are required in all patients. We report a case of an 18-year-old male child who was operated at the age of 6 months for lumbosacral myelomeningocele and was lost to follow-up and later presented with incontinence.